Perceived Desirability and Feasibility: Key Factors in Forming Entrepreneurial Intentions in Accounting Education - Ulfa Nurhayani; Sondang Aida Silalahi; Weny Nurwendari; Rini Herliani (Politeknik Ganesha Medan, 2025)
This research, titled